Anchored phylogenomics and a revised classification of the planidial larva clade of jewel wasps (Hymenoptera: Chalcidoidea). (10th January 2022) - Zhang, Junxia; Heraty, John M.; Darling, Christopher; Kresslein, Robert L.; Baker, Austin J.; Torréns, Javier; Rasplus, Jean‐Yves; Lemmon, Alan; Moriarty Lemmon, Emily
Abstract: Planidia are free‐living, mobile first‐instar larvae that are notable in their ability to transition across different larval stages of their host, and for completing their development on the host prepupa as ectoparasitoids, effectively acting as larval‐pupal external koinobionts. Chalcidoid taxa with a planidium form a monophyletic group, the planidial larva clade (PLC). We conducted a phylogenomic study of the PLC using anchored hybrid enrichment data. Phylogenetic analyses support the backbone relationship of PLC as: (Eutrichosomatinae, ((Philomidinae, Chrysolampinae), (Perilampinae, Eucharitidae))). Although excluded from the main analyses, the genus Jambiya, based on only 11 loci recovered, was placed as the sister of Chrysolampinae + Philomidinae or Perilampinae + Eucharitidae. Our results demonstrate that Perilampidae (Philomidinae, Chrysolampinae and Perilampinae) are paraphyletic. Divergence dating based on four node calibrations based on fossils suggests that the PLC arose approximately 111 Ma and the evolution of ant parasitism at least 64 Ma. Host associations, direct versus indirect hyperparasitism, ability to attack a host within a cocoon, soft versus hard planidial forms and mobility of the planidium were explored using a likelihood‐based ancestral state reconstruction method. A revised higher‐level classification of the PLC is proposed, with Eutrichosomatinae elevated to Eutrichosomatidae (stat. rev. ), Chrysolampinae and Philomidinae placed in Chrysolampidae (stat. rev. ), Perilampidae (stat. rev. ) restricted to what was referred to as Perilampinae, and Eucharitidae maintained with four subfamilies, with Akapalinae (unknown biology) as sister group to the core Eucharitidae, all of which are ant parasitoids. Jambiya is treated as an incertae sedis taxon within the planidial clade. Abstract : The planidial larva clade includes chalcidoid wasps with free‐living, mobile first‐instar larvae that attack the host larva and complete development as external parasitoids of the host pupa. Anchored hybrid enrichment data were used to analyse relationships among all major groups within the clade and result in changes to the classification. Ancestral states reconstruction proposes that a strongly sclerotized planidium arose twice within the clade, and both parasitism of ants and attacking ants with a cocoon each arose one time.